Depiction of trust in mother - Situmorang, Nina Zulida; Muhopilah, Pipih; Nasywa, Naila; Missasi, Vallahatullah (Indigenous, 2020)
Abstract. Mother is person who very close to her child, mother always caring and pay attention, this closeness creates child's trust to his mother. Trust is what makes children feeling that the mother is the most comfortable people to share all their complaints without demeaning. This study aims to explore the child's closeness with his mother and the reason. This research used qualitative research with constructive realism method, the subject of this research are 60 students that aged 20-28 years, the subject was asked: "how close to his mother and made a reason why the subject was close to his mother?". FGD was conducted on six-person subjects, and open interviews with 1 subject, data analysis using categorization method. The results of this study indicate that there are 6 categories of reasons children believe to mothers, which are caring (20.57%), understanding (20%), sincere (18%), attention (17.67%), patient (9.67%), resilient (9.35% ) and others (4.74%). The FGD results and interviews show that the main reason for child trust is mother caring and understanding, caring is shown by always trying to meet the children needs, giving a good example, and giving the best to his family. Understanding from mother makes child tell various things and accepted.Keywords: caring; mother; trust; understanding.